The role of partial denture in management of hypohidrotic ectodermal dysplasia - Tania Saskianti; Seno Pradopo; Prawati Nuraini; Michael Josef Kridanto Kamadjaja (Dental Journal (Majalah Kedokteran Gigi), 2008)
Ectodermal dysplasia is a rare hereditary disorder with a characteristic physiognomy. The ectodermal dysplasia constitutes a group of hereditary disorders whose clinical manifestation can be defects in ectodermal structures. The case of a 11-year-old child with hypohidrotic ectodermal dysplasia and partial anodontia is presented. Affected children require extensive dental treatment to restore appearance and help the development of a positive self image. Partial denture was provided to encourage a normal psychological development and to improve the function of the stomatognatic system. It is important for the patient and the dentist to understand that continued monitoring for dental problems is necessary. This paper had an objective to relate and discuss a case of hypohidrotic ectodermal dysplasia, with the approach of the influence of an esthetic rehabilitation and functional alternative in the improvement of the quality of life.